(untitled) (Nexus International Journal of Science and Education, 2024)
The study unfolded to assess the extent of the efficacy of individualized educational plans of special education outcomes in Paquibato District, Schools Division of Davao City. This used a non-experimental descriptive-correlational research design, utilizing an adapted survey instrument to gather responses from the randomly selected teacher-respondents. Data gathered were treated using Mean scores with descriptive interpretation, Pearson r, and Simple Linear Regression Analysis. Findings revealed that the extent of the efficacy of individualized educational plans in terms of behavioral improvement, inclusion, and social integration are oftentimes manifested; while parent-teacher collaboration, goal attainment, and academic progress are sometimes manifested, while the extent of special education outcomes in terms of transition outcomes, behavioral and social skills and alignment with organizational goals are oftentimes manifested; while, parent -guardian satisfaction is sometimes manifested. A significant correlation exists between the efficacy of individualized educational plans and special education outcomes. All domains of individualized educational plans regarding academic progress, goal attainment, behavioral improvement parent, parent-teacher collaboration and inclusion, and social integration suggest significant influence over special education outcomes. Future research may create a collaborative culture among teachers to share insights, resources, and effective instructional strategies.